'Song of Life': music therapy in terminally ill patients with cancer - Warth, Marco; Keßler, Jens; Ditzen, Beate; Bardenheuer, Hubert J. (BMJ Supportive & Palliative Care, 2018)
Abstract: Objectives Music therapy (MT) holds a promising potential to meet emotional and existential needs in palliative care patients. The aim of the present pilot study was to assess the feasibility, acceptance and potential effectiveness of a novel MT intervention to improve life closure and spiritual well-being of terminally ill patients with cancer receiving palliative care. Methods: The ‘Song of Life’ (SOL) intervention was provided on two consecutive sessions containing a biographical interview and a live performance of a song with high biographical relevance to the patient in a lullaby style. Pre-to-post intervention assessments comprised brief self-report measures on life closure, well-being, stress, worry and pain. Results: 13 out of 15 patients were able to complete the protocol as intended. The chosen songs were associated with a close person, an important place or event or with a religious belief. The results showed medium-sized improvements with regard to life closure, well-being, relaxation, worry and pain. Conclusion: ‘SOL’ proved to be a feasible and highly accepted intervention for patients approaching the end of their lives. Further consideration with regard to the procedures and outcomes is necessary before implementation of a randomised trial.
Gesehen am 27.06.2019